PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LIKUIDITAS, UMUR PERUSAHAAN DAN FINANCIAL LEVERAGE TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Real Estate Dan Property Yang Terdaftar Di BEI Tahun 2010-2013) - Ariani Rachmawati, 11.05.52.0097; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2015)
This study aims to find empirical evidence about the factors that affect the timeliness of financial reporting on Real Estate and Property companies listed in Indonesia Stock Exchange (IDX). In this study, the methods used in sampling was purposive sampling method. The dependent variable in this study is timely submission of financial statements, while the independent variable is profitability, firm size, liquidity, financial leverage and firm age. Data analysis tool used is descriptive statistics and methods of data analysis is logistic regression. The results of the study identified that profitability, firm size, significantly influence the timeliness of financial statements of the company, while the variable liquidity, financial leverage and firm age does not affect the timeliness of financial statements Real Estate & Property companies listed in Indonesia Stock Exchange (IDX).Keywords: Timeliness (timeliness), Profitability, Firm Size, Liquidity, Financial Leverage and Firm Age